Implementasi Nilai-Nilai Piil Pesenggiri Sebagai Basis Moderasi Beragama Pada Masyarakat Adat Pepadun Di Bandar Lampung - Badiah, Siti; Meisuri (Universitas Islam Negeri Raden Intan Lampung, 2024)
Lampung people have a culture that uses symbols and identity to regulate how to behave in community life which is interpreted as local wisdom called Piil Pesenggiri. Piil Pesenggiri as local wisdom has made the Lampung area special, because it is a way of life or basic values for the Lampung tribal people. Piil Pesenggiri consists of Juluk Adek (the principle of a person's success which is obtained by maintaining the traditional title attached to that person), Nemui Nyimah (the principle of respect for guests or newcomers), Nengah Nyampur (the principle of social relations as a continuation of Nemui Nyimah) and Sakai Sembayan (the principle of cooperation and mutual assistance). These four elements of Piil Pesenggiri, apart from being used as an identity or way of life for the community, are also used as a value of inter-ethnic tolerance. The Indonesian government, through the Ministry of Religion, is actively implementing a religious moderation movement. This is understandable because the government sees that the conflict that occurs in Indonesia is one of the causes because people tend to be exclusive but are not placed in the right portion. With the condition of a pluralistic society, this Community Service activity is emphasized on understanding religious moderation with a harmonious living atmosphere through the local wisdom of Piil Pesenggiri. Key words: Religious Moderation. Local Wisdom, Piil Pesenggiri